Logos and life : essays on mind, action, language and ethics - Teichmann, Roger (Anthem Studies in Wittgenstein, 2022)
The essays in Logos and Life cover topics in philosophy of mind, philosophy of action, ethics and philosophy of language. Several take as their starting points the ideas of Wittgenstein and of Elizabeth Anscombe. They will be of interest to anyone studying these philosophers.